The Relationship between Socio-Demographic Characteristics, Safety Awareness, and Safety Behaviors among Workers in E-Waste Recycling Shops in Thailand - Somsiri Decharat; Peeranart Kiddee (Occupational Health and Safety Society of Nepal, 2024)
Introduction: Safety behavior is an approach to workplace safety that focuses on workers' behavior as the cause of most work-related injuries and illnesses. Some of the effects of e-waste recycling on health may occur. Methods: A cross-sectional study was conducted between January and July 2021 with e-waste workers living in Southern Thailand. The questionnaire was divided into 3 parts:  1) socio-demographic characteristics for 14 items; 2) safety awareness for 20 items; and 3) safety behaviors for 20 items, collected data from e-waste workers. Interpreting The average score value was interpreted using the interpretive criteria divided into three levels. Descriptive and multilinear regression analyses were conducted. P < 0.05 was considered statistically significant.                    Results: The results of this study found that the majority of e-waste workers were male (96.30%). E-waste workers who smoked cigarettes, drank alcohol, worked ≥ 8 hours per day, ≥6 days/week, and had worked for >13 years had significantly lower safety behavior practice levels compared to e-waste workers who did not smoke cigarettes, did have drank alcohol, worked < 8 hours per day, < 6 days/week, and ≤13 years. Health effects on e-waste workers in e-waste recycling shops were significantly associated with hours worked per day, days worked per week and the use of masks and gloves. In addition, significant relationships were found between safety behaviors and safety awareness (F: 597.457; P < .001).                                                                                          Conclusion: Safety behavior is very important. Meanwhile, raising awareness with safety factors in mind is important because it makes safety behaviors sustainable.